The evolution of mild parkinsonian signs in aging - Mahoney, Jeannette R. (J Neurol, 2014)
The progression of mild parkinsonian signs in the absence of idiopathic Parkinson’s disease in aging is unclear. This study aims to identify predictors of the evolution of mild parkinsonian signs in non-demented older adults. Two hundred ten participants (76.25 ± 7.10 years, 57 % women) were assessed at baseline and 1-year follow-up. Mild parkinsonian signs were defined as the presence of bradykinesia, rigidity and/or rest tremor. Depending upon the presence of these features at baseline and follow-up, participants were divided into one of four groups (no, transient, persistent or new-onset mild parkinsonian signs). Physical function was assessed using gait velocity. Ninety-five participants presented with mild parkinsonian signs at baseline. At 1-year follow-up, 59 demonstrated persistent mild parkinsonian signs, while 36 recovered (i.e., transient). Participants with persistent mild parkinsonian signs were older (79.66 ± 7.15 vs. 75.81 ± 7.37 years, p = 0.01) and evidenced slower gait velocity (90.41 ± 21.46 vs. 109.92 ± 24.32 cm/s, p < 0.01) compared to those with transient mild parkinsonian signs. Gait velocity predicted persistence of mild parkinsonian signs, even after adjustments (OR: 0.96, 95 % CI: 0.94–0.98). Fifty-five participants demonstrated new-onset of mild parkinsonian signs. In comparison to participants without mild parkinsonian signs, presence of cardiovascular but not cerebrovascular disease at baseline was associated with new-onset mild parkinsonian signs. Our study reveals that gait velocity was the main predictor of persistent mild parkinsonian signs, whereas cardiovascular disease was associated with new-onset mild parkinsonian signs. These findings suggest a vascular mechanism for the onset of mild parkinsonian signs and a different mechanism, possibly neurodegenerative, for the persistence of mild parkinsonian signs.